Ad-Dakhil Dalam Tafsir Al-Mazhari (Studi Analisis Terhadapa QS Saba’) - Rizka Abidah (Yayasan Pondok Pesantren Rasyidiyah Khalidiyah Amuntai, 2026)
Identifying dakhil in tafseer is a methodological imperative for scholars and experts engaged in the field of tafseer. This study aims to trace the presence of dakhil in tafseer al-Mazhari, specifically in Surah Saba’, while also constructing a critique of the interpretive errors found therein. This quantitative study comprehensively examines all verses and their interpretations, particularly the hadiths used in interpreting the verses, as well as opinions related to fiqh, aqidah, and language. The collected data was analyzed using a descriptive-analytical method. The primary source is the Tafseer al-Mazhari by Muhammad Tsana’ullah al-Mazhari, which was cross-referenced with various authoritative classical texts as secondary sources. The results of this study indicate that there is Dakhil infiltration in Surah Saba’, specifically the presence of Israiliyat and weak hadiths that do not meet the criteria to serve as evidence. Following these findings, this study recommends the need for a more comprehensive expansion of Dakhil-critical studies of Tafseer al-Maẓharī in other surahs.